2017
DOI: 10.1007/s12602-017-9365-8
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Kefir-Fermented Sheep’s Milk, a Source of Antimicrobial and Antioxidant Peptides

Abstract: Fermented milks are a source of bioactive peptides and may be considered as functional foods. Among these, sheep's milk fermented with kefir has not been widely studied and its most relevant properties need to be more thoroughly characterized. This research study is set out to investigate and evaluate the antioxidant and antimicrobial properties of peptides from fermented sheep's milk in Brazil when produced by using kefir. For this, the chemical and microbiological composition of the sheep's milk before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 42 publications
3
28
1
9
Order By: Relevance
“…At the end of the storage period (day 20), the pH of goat and camel kefir samples decreased to 3.65 ± 0.07 and 3.25 ± 0.05, respectively, while that of sheep and cow kefirs reached 4.02 ± 0.07 and 4.19 ± 0.03 (P < 0.01). It is reported that the pH of sheep milk kefir decreased from 4.50 to 3.70 during the 28-day storage period 12 , which showed more pH changes compared to our results for sheep kefir. Yilmaz-Ersan et al found that the pH of cow kefir was slightly higher in comparison to sheep kefir 13 , which is similar to our results.…”
Section: Resultscontrasting
confidence: 67%
“…At the end of the storage period (day 20), the pH of goat and camel kefir samples decreased to 3.65 ± 0.07 and 3.25 ± 0.05, respectively, while that of sheep and cow kefirs reached 4.02 ± 0.07 and 4.19 ± 0.03 (P < 0.01). It is reported that the pH of sheep milk kefir decreased from 4.50 to 3.70 during the 28-day storage period 12 , which showed more pH changes compared to our results for sheep kefir. Yilmaz-Ersan et al found that the pH of cow kefir was slightly higher in comparison to sheep kefir 13 , which is similar to our results.…”
Section: Resultscontrasting
confidence: 67%
“…Due to the action of microorganisms and endogenous proteolytic enzymes, PAs can be produced during the fermentation process [124,125]. Many kinds of fermented milk have been proven to be an important source of bioactive peptides [126][127][128]. Four peptides with high antioxidant activity in both chemistry and cell model evaluations have been purified and identified from the pasteurized milk fermented with Lactobacillus acidophilus NCFM ® , Lactobacillus delbrueckii subs.…”
Section: Microbial Fermentation and Other Food Processingmentioning
confidence: 99%
“…It is a fermented milk drink produced from kefir grains containing microorganisms in a complex and specific mixture of polysaccharide matrix, which has a fresh and slightly acidic taste. Kefir is usually produced from cow's milk, but it can also be successfully made from sheep milk (Larosa et al, 2021a;de Lima et al, 2018), buffalo milk (Tomar et al, 2020) and colostrum (Setyawardani, et al, 2020). This fermented milk drink is different from other fermented milk products in terms of the complex Effect of milk kind on the physicochemical and sensorial properties of synbiotic kefirs containing Lactobacillus acidophilus LA-5 and Bifidobacterium bifidum BB-11 accompanied with inulin metabolic activity based on several microbial species as well as the production methods of the kefir grains (Farnworth & Mainville, 2008).…”
Section: Introductionmentioning
confidence: 99%